Bris soil temperature [under bare surface; pastures; Cocos nucifera; Anacardium occidentale] - Abdul Wahab Nafis (2013)
This study indicated that the bris soil temperature under four different conditions were in the order of bare surface under pasture (guinea grass) under coconut trees under cashewnut trees. The daily range soil temperature was lowest under cashew trees, about 3.5 deg C while under bare soil surface about 10.7 deg C (highest). Bris soil temperatures were high during the dry period especially in March and low in the monsoon season (Nov-Dec). Surface temperature of Baging series was found to be slightly higher than Rudua and Jambu series. Lalang mulching significantly decreased the surface soil temperature between 5 deg C and 6 deg C in the afternoon. Chilli yields were also improved about 12% to 49% when mulched